Evaluation of Anti-inflammatory Effects of Extract Maggot Black Soldier Fly (Hermetia illucens L.) in vitro study - Rahayu, Resti; Efendi, Rilwan; Santoso, Putra (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Inflammation is the body's normal protective response, but it is often an over-response that can cause tissue damage. Commercial synthetic anti-inflammatory drugs of steroidal and non-steroidal groups have high side effects. So that alternative anti-inflammatory drugs are needed that have low side effects. Maggot black soldier fly is a type of insect that has begun to be widely studied to utilize its bioactives as anti-inflammatory, one of which is because it is high in protein. Therefore, this study aims to explore the anti-inflammatory properties of black soldier fly maggot extract. Anti-inflammatory testing of maggot extract was carried out using an in vitro heat-induced protein denaturation assay, with diclofenac sodium serving as a commercial drug reference. It was found that maggot extracted with 100% methanol was 5 times more effective than maggot extracted with other methanol concentrations. Amino acid analysis showed increased levels of alanine and arginine, which are believed to contribute to the inhibition of protein denaturation. Thus, maggot extracted with 100% methanol showed better potential as an anti-inflammatory drug.